The financial performance common size and ratio analysis case study of MISC Bhd / Norhaniza Mohomad Osman - Mohomad Osman, Norhaniza (Faculty of Business and Management, 2011)
All companies gather financial data about their operations and report this information in financial statements for interested parties. These statements are widely standardized, and so we can use the data in them to make comparisons between firms and over time. An annual report provides four basic financial statements: the balance sheet, the income statement, the statement of cash flows, and the statement of retained. Ratio analysis involves methods of calculating and interpreting financial ratios to analyse and monitor the firm’s performance. The basic inputs to ratio analysis are the firm’s income statement and balance sheet. The researcher would focus on the reveals financial statements to evaluate the MISC BHD’s financial position by using ratio analysis and the common size analysis. The researcher focuses more on the profitability ratio, leverage ratio, and profitability ratio. By analyse the income statement by using common statement analysis, it shows the profitability in which the profit percentage of the sales shows how many profits of the sales. From the case study, it shows that the company’s issues were on the profitability and the leverage. The profitability worsening decreases even though it is increase in the total assets. The total assets increase because on the issuing of the right issue that increase the capital expenditure. It shows that the company not full utilizes their asset to generate profits. From income statement analysis, it shows that profit of sales decreasing, in which this support the figure on the shrunk of company’s profitability as a 2010.